Violence : the enduring problem - Alvarez, Alex; Bachman, Ronet (Los Angeles: SAGE, 2021)
"The Fourth Edition of Violence: The Enduring Problem offers an interdisciplinary and reader-friendly exploration of the patterns and correlations of individual and collective violent acts using the most contemporary research, theories, and cases. Responding to the fear of pervasive violence in the world, authors Alex Alvarez and Ronet Bachman address the various legislative, social, and political efforts to curb violent behavior. They expertly incorporate a wide range of the most current cases to help readers interpret the nature and dynamics of a variety of different, yet connected, forms of violence. While most texts of this type simply cover individual acts of violence, this book offers readers a broader perspective, covering more collective violence activities such as terrorism, mob violence, and genocide. ? KEY FEATURES In Focus boxes provide personal narratives, case studies, and related information to enhance the chapter coverage. Broad coverage addresses legislative, social, and political efforts to curb violent behavior. Both individual and collective forms of violence are examined and, unlike other texts on the subject, the book illustrates the linkages between these two general types of violent acts. The interdisciplinary approach draws from a number of different disciplines including criminology and criminal justice, sociology, psychology, political science, and public health"--
Revised edition of the authors' Violence, [2017]
Includes bibliographical references and index.
Keywords: Violence -- United States; Violent crimes -- United States; Violence; Aggressiveness; Genocide